"America's Mandela": South African responses to the rise of Barack Obama - Du Pisani, Jacobus A.; Kim, Kwangsu (Faculty of Humanities, University of the Free State, 2013)
In this article reactions in the South African media to the emergence of Barack Obama as contender in the 2008 US presidential election, then as official Democratic Party presidential candidate and then as US President-elect are analysed. The context of US-SA relations is sketched first to highlight the type of issues of US-SA relations that would be important for South Africans. Then the opinions of politicians, economists, editors, academics and letter-writers representing the public, which were published in South African newspapers in 2008 and 2009 at the crucial moments in the US presidential election campaign, are analysed in terms of perceptions about Obama's role in international affairs, US relations with Africa and bilateral USA-RSA relations. The evaluation of these South African opinions is done with a view to testing some conclusions reached in the literature on the process of globalization and local responses to it. Our argument is that the analysis of South African responses to Obama published in the newspapers confirms that globalization and glocalisation are simultaneous processes in the contemporary world. On the one hand a set of liberal moral values have emerged in the post-Cold War world which unites the majority of moderate citizens of countries across the globe in their evaluation of important events. On the other hand these generic values only assume real significance for people when their implications for the local situation become clear.
Keywords: Barack Obama; USA presidential election 2008; SA Media; Opinions; Globalisation; Glocalisation; USA-RSA relations; Newspapers